Radiographic Measurement of Cochlear Duct Length in an Indian Cadaveric Population - Importance of Custom Fit Cochlear Implant Electrodes - Singh, Anup; Kumar, Rajeev; Manchanda, Smita; Bhalla, Ashu Seith; Sagar, Prem; Irugu, David Victor Kumar (International Archives of Otorhinolaryngology, 2020)
Introduction Successful cochlear implantation requires an appropriate insertion depth of the electrode, which depends on cochlear duct length CDL). The CDL can vary due to ethnic factors.Objective The objective of the current study was to determine the CDL in an Indian adult cadaveric population.Methods The present was a cadaveric study using the temporal bones obtained after permission of the Institutional Review Board. The temporal bones were subjected to high-resolution computed tomography (HRCT), and the double oblique reformatted CT images were reconstructed through the basal turn of the cochlea. The reformatted images were then viewed in the minimum-intensity projection (minIP) mode, and the ‘A’ value (the diameter of the basal turn of the cochlea) was calculated. The CDL was then measured using the formula CDL = 4.16A - 4 (Alexiades et al). The data analysis was performed using the Microsoft Excel software, version 2016.Results A total of 51 temporal bones were included for imaging analysis. The CDL varied from 27.6 mm to 33.4 mm, with a mean length of 30.7 mm. There was no statistically significant difference between the two sides.Conclusion The CDL can be calculated with preoperative high-resolution CT, and can provide a roadmap for effective cochlear implant electrode insertion. The population-based anatomical variability needs to be taken into account to offer the most efficient and least traumatic insertion of the electrode.
Keywords: cochlear implantation; cochlear duct; tomography; adult; cadaver